2019
DOI: 10.1101/784579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell transcriptomics of human epidermis reveals basal stem cell transition states

Abstract: How stem cells give rise to human interfollicular epidermis is unclear despite the crucial role the epidermis plays in barrier and appendage formation. Here we use single cell-RNA sequencing to interrogate basal stem cell heterogeneity of human interfollicular epidermis and find at least four spatially distinct stem cell populations that decorate the top and bottom of rete ridge architecture and hold transitional positions between the basal and suprabasal epidermal layers. Cell-cell communication modeling thro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 123 publications
(117 reference statements)
0
7
0
Order By: Relevance
“…CCC analysis also elucidated how erythroblasts interact with macrophages during haematopoiesis in the fetal liver 23 and was applied to liver organoid development to investigate how multilineage communication shapes the differentiation of hepatic cells 24 . Following similar principles, other studies have used CCC analyses to understand differentiation during epidermal regeneration 25 27 , development of the interfollicular epidermis 28 and formation of the maternal–fetal interface in early pregnancy 29 , 30 .…”
Section: Insights From Rna-based CCI Analysesmentioning
confidence: 99%
“…CCC analysis also elucidated how erythroblasts interact with macrophages during haematopoiesis in the fetal liver 23 and was applied to liver organoid development to investigate how multilineage communication shapes the differentiation of hepatic cells 24 . Following similar principles, other studies have used CCC analyses to understand differentiation during epidermal regeneration 25 27 , development of the interfollicular epidermis 28 and formation of the maternal–fetal interface in early pregnancy 29 , 30 .…”
Section: Insights From Rna-based CCI Analysesmentioning
confidence: 99%
“…In the interfollicular epidermis of human skin, stem cells reside at the basal layer and exhibit cell heterogeneity (8). Our study revealed two keratinocyte clusters, KC_2 and KC_4, both of which strongly express the known basal keratinocyte signature, that is, KRT14, ITGA6, and ITGB1 (23, 24) (Figure 2I).…”
Section: Molecular Features Of Epidermal Keratinocytesmentioning
confidence: 73%
“…This dataset can be explored at a free, browsable web portal (https://www.xulandenlab.com/data). The advancement of single-cell RNA sequencing (scRNA-seq) technology has enabled the generation of molecular maps of human tissues at an unprecedented resolution, and this technology has recently been used to characterize human skin (5)(6)(7)(8) and related diseases, such as psoriasis (5), atopic dermatitis (9), and melanoma (10), as well as fibroblast heterogeneity (11) and epidermal stem cells (12,13) in murine wound models. Although rodent wound models exhibit a wound healing procedure similar to that of humans, they cannot fully reflect the complexity of disordered wound healing in humans (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains elusive whether only cells that occupy specific niches or locations relative to the underlying dermis have SC properties, or if in principle all IFE basal cells are equally capable of responding to inductive signals and thus can serve as IFE SCs [9,109,110]. In human skin, earlier studies concluded that adult IFE SCs unlikely occupy specific locations in the basal epidermal layer [111,112], while recent single-cell RNA sequencing (scRNA-seq) analysis of human neonatal foreskin identified four basal cell subsets and the study overall suggests that specific niches may exist depending on the proximity to the so-called rete ridges (protrusions of the epidermis extending downwards into the dermal layer), with one population possibly associated with papillary fibroblasts [113]. In mouse skin, scRNA-seq identified two robust basal epidermal subsets of IFE cells (regardless of cell cycle) which differ in expression levels of typical basal epidermal genes (e.g.…”
Section: Touch Dome Ife (Hf Opening)mentioning
confidence: 99%